Emotion word processing: does mood make a difference? - Sereno, Sara C.; Scott, Graham G.; Yao, Bo; Thaden, Elske J.; O'Donnell, Patrick J. (Frontiers in Psychology, 2015)
Visual emotion word processing has been in the focus of recent psycholinguistic research. In general, emotion words provoke differential responses in comparison to neutral words. However, words are typically processed within a context rather than in isolation. For instance, how does one’s inner emotional state influence the comprehension of emotion words? To address this question, the current study examined lexical decision responses to emotionally positive, negative, and neutral words as a function of induced mood as well as their word frequency. Mood was manipulated by exposing participants to different types of music. Participants were randomly assigned to one of three conditions – no music, positive music, and negative music. Participants’ moods were assessed during the experiment to confirm the mood induction manipulation. Reaction time results confirmed prior demonstrations of an interaction between a word’s emotionality and its frequency. Results also showed a significant interaction between participant mood and word emotionality. However, the pattern of results was not consistent with mood-congruency effects. Although positive and negative mood facilitated responses overall in comparison to the control group, neither positive nor negative mood appeared to additionally facilitate responses to mood-congruent words. Instead, the pattern of findings seemed to be the consequence of attentional